RegulonDB: a database on transcriptional regulation in Escherichia coli. - Huerta, A M (1998)
RegulonDB is a DataBase that integrates biological knowledge of the mechanisms that regulate the transcription initiation in Escherichia coli , as well as knowledge on the organization of the genes and regulatory signals into operons in the chromosome. The operon is the basic structure used in RegulonDB to describe the elements and properties of transcriptional regulation. The current version contains information around some 500 regulation mechanisms, essentially for sigma 70 promoters.